Deep Venous Thrombosis With Symptomatic Bilateral Pulmonary Embolism After Using an Infrapatellar Strap for Patellofemoral Pain in an Athletic Cardiothoracic Surgeon. Issue 6 (November 2021) - Segers, Patrique; Hendriks, Babs M. F.; Heuts, Samuel
Abstract : Abstract: Knee braces and patellar straps are frequently prescribed devices for treatment of patellofemoral pain syndrome. In this report, we describe the occurrence of localized deep venous thrombosis (DVT) after use of an infrapatellar strap. Until now, external mechanical compression has not been recognized as a cause of DVT. In young and athletic patients presenting with DVT, after exclusion of the most prominent risk factors, untraditional causes should be considered to mistakenly label a DVT as unprovoked. Abstract : Supplemental Digital Content is Available in the Text.